2016
DOI: 10.1364/oe.24.023798
|View full text |Cite
|
Sign up to set email alerts
|

Wide-angle nonmechanical beam steering using liquid lenses

Abstract: Nonmechanical beam steering is a rapidly growing branch of adaptive optics with applications such as light detection and ranging, imaging, optical communications, and atomic physics. Here, we present an innovative technique for one- and two-dimensional beam steering using multiple tunable liquid lenses. We use an approach in which one lens controls the spot divergence, and one to two decentered lenses act as prisms and steer the beam. Continuous 1D beam steering was demonstrated, achieving steering angles of ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…The divergence angle should be increased in accordance with the amplification of deflection angle, which could be resolved by vertically stacking additional lenses. [ 48,76,77 ] Moreover, by replacing the uniformly long RDRs with polarization‐dependent 2D nanoposts, which are popularly used for metasurface devices, an unprecedented MD could be developed to enhance the device efficiency and accommodate other prominent functions such as lens focusing, vortex beam generation, and holograms. [ 27–30,32,33 ]…”
Section: Resultsmentioning
confidence: 99%
“…The divergence angle should be increased in accordance with the amplification of deflection angle, which could be resolved by vertically stacking additional lenses. [ 48,76,77 ] Moreover, by replacing the uniformly long RDRs with polarization‐dependent 2D nanoposts, which are popularly used for metasurface devices, an unprecedented MD could be developed to enhance the device efficiency and accommodate other prominent functions such as lens focusing, vortex beam generation, and holograms. [ 27–30,32,33 ]…”
Section: Resultsmentioning
confidence: 99%
“…One such example is cascaded lenses. Previous works have shown that, by stacking liquid lenses in a de-centered manner, large steering angles can be achieved [34]. This concept may apply to LC lenses, as well.…”
Section: Operation Principles Of Lc Beam Steeringmentioning
confidence: 91%
“…This paper is concerned more with devices that manipulate phase rather than control the phase in an absolute sense but will also mention interesting alternatives. One such interesting approach was taken by Zohrabi et al 7 who used a series of tunable liquid lenses to implement beam steering. Steering in one dimension (1D) is accomplished by offsetting the optical axes of 2 tunable lenses and then controlling the focusing power of both lenses to focus the transmitted beam in a fixed focal plane.…”
Section: Non-mechanical Beam Steeringmentioning
confidence: 99%